Heads up reconstructive microsurgery: Utilisation of the three-dimensional microscope in microvascular procedures. Issue 2 (February 2022) - Sleiwah, A; Mohanna, P; AsJoe M, Ho; Roblin, P; Uppal, L; Mughal, M
Abstract: Background: : Since the earliest use of microscopes in surgery, several modifications have been made to improve the ergonomics of movement and posture, increase the resolution, and expand the visual field. The three-dimensional microscopes are latest innovation in this field. Despite the wider use of 3D microscopes in other specialities, their use in the reconstructive microsurgery in the United Kingdom is still limited. Reconstructive microsurgeons are highly skilled surgeons that are trained to operate utilising the microscope for long hours. This poses an occupational risk with a specific pattern of work-related conditions. Aims and methods: : We aim in this report to demonstrate our experience utilising 3D microscopes in small cohort of patients matched to a control of patients operated utilising the traditional microscopes. Patients were matched by age, comorbidities, oncologic procedures. This was complemented by a survey completed by the operating surgeons. Results: : Nine patients were included in each group. There was no significant difference in operative or ischemia time and no significant post-operative complications in both groups. The surgeons reported better ergonomics, improved staff engagement, and a better teaching experience when utilising the 3D microscopes compared to traditional microscopes. Conclusion: : The utilisation of the 3D microscopes in reconstructive microsurgery has shown to provide comfort, improve ergonomics of movement and posture without significant clinical implications in this series.